Chip-based measurement-device-independent quantum key distribution using integrated silicon photonic systems - Cao, Lin (2020)
Measurement-device-independent (MDI) quantum key distribution (QKD) employs an untrusted relay to prevent the receiver from side-channel attacks commonly encountered in earlier QKD protocols. Conventional MDI QKD systems rely entirely on bulky and expensive optical setups that present great challenges for system scaling and integration. In this work, an all-chip-based MDI QKD system including two transmitter chips and one server chip is demonstrated using integrated silicon photonic technology. The system is capable of generating polarization-encoded weak coherent states with polarization extinction ratios of over 20 dB, sufficient for low-error MDI QKD. In the proof-of-concept experiment, the chip-based MDI QKD system generates a key rate per pulse of 2.923×10−6 over a distance corresponding to a 50-km standard fiber with 25% detection efficiency and a predicted distance of 120 km with 85% detection efficiency. Our proof-of-concept prototype makes a giant step forward towards fully chip-based MDI QKD systems and highly integrated quantum communication networks in the near future with its high scalability and cost effectiveness.